MANTLE XENOLITHS AND THICK LITHOSPHERE IN THE FENNOSCANDIAN SHIELD - Kukkonen I.T.; Kinnunen K.A.; Peltonen P. (My University, 2003)
We applied data on kimberlite-hosted mantle xenoliths from Lahtojoki, Kaavi, in eastern Finland for thermal, rheological and seismic velocity modeling of the lithospheric mantle in the central part of the Fennoscandian Shield. We also report petrographic evidence for decrepitated fluid inclusions indicating a presence of fluids in the upper mantle. Our data and models suggest that the thermal and rheological lithosphere is very thick (230–250 km), contains small amounts of fluids, and follows wet (but not fluid-saturated) olivine rheology. The lithospheric part of the mantle where heat transfer is mainly conductive and which does not participate in convection, changes into a mechanical asthenosphere in a solid state. Mantle viscosity shows a weak minimum at the mechanical lithosphere–asthenosphere boundary. The lithosphere–asthenosphere transition does not require partial melting, and very probably there is no partial melt-bearing asthenosphere beneath the lithosphere at all. This also precludes an electrical asthenosphere in the sense of high conductivity due to partial melting. Seismic velocity models calculated using data on mineral composition of the xenoliths and mineral elastic parameters indicate no low-velocity layer at the lithosphere–asthenosphere boundary, instead only a downward increase in the vertical velocity gradients. The velocity model indicates velocities higher than iasp91 (up to 2%) at depths above 250 km, and it is in good agreement with seismic body-wave tomography results.